Does specialization make you happier? A study on the relationship between the degree of job specialization and job satisfaction - Chai, Nicholas Chen Yee (Nanyang Technological University, 2023)
The Economics of happiness & wellbeing is a hot topic. Ever since the early 20th century, empirical studies on happiness related literature have thrived substantially. The pursuit of happiness is viewed as a core value in life, and studies examining the relationship between happiness and other associated factors such as income, career, and social status are becoming increasingly common. Given that our job forms a substantial part of our lives, much literature has surfaced to examine the bridge between happiness and job. The most contentious debates stemmed from the areas of income, work-life balance, even work culture, and how they can determine one’s happiness and satisfaction. In our paper, we aim to investigate how the nature of jobs play a role in determining one’s sense of satisfaction. More specifically, we seek to examine the relationship between the degree of job specialization and job satisfaction. We hypothesize that the less specialized an individual is in his or her job, the more well-equipped he or she is in terms of the sheer magnitude of opportunities, skills, and abilities. Rather than feeling monotonous in a specialized area, the workers get to expose themselves to job rotation opportunities. Also, they get to take on more challenging projects and roles which reduces boredom and repetitiveness. Workers also get to pick up new skills, abilities and connections along the way, thereby enhancing personal growth and job satisfaction. Through the cross-analysis of secondary data gathered from HILDA (The Household, Income, and Labour Dynamics in Australia) and our survey questionnaire, we seek to test the hypothesis, and draw further insights between job specialization and job satisfaction. We believe that our findings are relevant to both job seekers and employers. We hope that our insights would necessitate a more balanced workplace with greater workplace satisfaction.